أهمية استخدام الذكاء الاصطناعي في تحسين نظام المعلومات المحاسبي دراسة ميدانية لمؤسسات اقتصادية بالوادي - نور الإسلام شريط; شيماء بن ناصر; نبيلة بدين (university of eloued جامعة الوادي, 2025)
" تهدف هذه الدراسة إلى استكشاف أهمية استخدام الذكاء الاصطناعي في تحسين نظام المعلومات المحاسبي بالمؤسسات الاقتصادية في ولاية الوادي، في ظل التغيرات المتسارعة في بيئة العمل. وبالاعتماد على المنهج الوصفي التحليلي واستبيان شمل عينة مكوّنة من 45 مفردة، توصلت النتائج إلى أن مستوى تحسين نظام المعلومات المحاسبي كان عالياً، كما تبيّن وجود أثر إيجابي لمختلف أبعاد الذكاء الاصطناعي (التعلم الآلي، معالجة البيانات، الأمان السيبراني، ودعم اتخاذ القرار) في تعزيز فعالية وكفاءة النظام المحاسبي. وقد أكدت الدراسة الدور الهام لاستخدام الذكاء الاصطناعي في تطوير نظم المعلومات المحاسبية بالمؤسسات الاقتصادية. This study explores the role of artificial intelligence (AI) in enhancing accounting information systems in economic institutions in El Oued, amid rapid changes in the work environment. Using a descriptive and analytical method, a questionnaire was administered to a sample of 45 participants. The results indicated a high level of improvement in the accounting system. Additionally, the study found a positive impact of AI dimensions—such as machine learning, data processing, cybersecurity, and decision-making support—on the system’s efficiency and effectiveness. The findings highlight the importance of AI in developing accounting systems and supporting operational performance in modern institutions.
ماستر
Keywords: الذكاء اصطناعي; النظام معلومات محاسبي; لتعلم الآلي; Artificial intelligence; Accounting information system; Machine learning